The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/drones7070425
|View full text |Cite
|
Sign up to set email alerts
|

Particle Deposition Distribution of Multi-Rotor UAV-Based Fertilizer Spreader under Different Height and Speed Parameters

Abstract: As an effective supplement to ground machinery, UAVs play an important role in agriculture and have become indispensable intelligent equipment in the development of precision agriculture. Various types of agricultural UAV-based spreading devices, mainly disc-type and pneumatic-type, have appeared in domestic and foreign markets. UAV-based rice topdressing has gradually become a widely recognized application with great market potential. In the process of UAV-based low-altitude fertilization, due to the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Fluid flow, spray uniformity, and working width control. As shown in [7,11,35], these parameters are controlled by the flight speed and altitude of the UAV. In [11], it is shown that by varying the UAV flight speed in the range of 10 to 50 km/h and the flight altitude from 1 to 5 m, it is possible to control the fluid flow from 1 to 5 L/min.…”
Section: Implementing Ulv Technology With Uavsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluid flow, spray uniformity, and working width control. As shown in [7,11,35], these parameters are controlled by the flight speed and altitude of the UAV. In [11], it is shown that by varying the UAV flight speed in the range of 10 to 50 km/h and the flight altitude from 1 to 5 m, it is possible to control the fluid flow from 1 to 5 L/min.…”
Section: Implementing Ulv Technology With Uavsmentioning
confidence: 99%
“…By analyzing Table 9, it is evident that the thickness of the film containing the PPA can be adjusted by increasing the speed and altitude of the UAV. This relationship is explained in [35], where the opening of the spray cone changes in response to increasing speed or altitude, which ultimately changes the coating surface and subsequently the film thickness. The accuracy of the data presented in Tables 8 and 9, and therefore the conclusions drawn, are supported by field experiments [11,72].…”
Section: Implementing Ulv Technology With Uavsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, Faiçal et al [12] integrated ground sensors with UAV spraying, dynamically adjusting flight parameters based on measured environ mental parameters to achieve more uniform pesticide spraying. Song et al [13] optimized the distribution of fertilizer particle deposition under different flight altitudes and speeds of multi-rotor UAVs during fertilization, ensuring a reasonable and effective deposition amount during actual fertilization processes. Furthermore, Gu et al [14] explored the in fluence of different flight parameters on point cloud data quality, revealing a positive cor relation between the root mean square error of the airborne lidar flight trajectory and fligh altitude and speed.…”
Section: Introductionmentioning
confidence: 99%
“…They can perform tasks such as soil analysis [30][31][32], seedling density tracking [33,34], weed and pest detection and classification [35][36][37][38], yield prediction [39][40][41], and harvest readiness assessment. In some rare cases, UAVs can be used for harvesting, precision fertilization [42][43][44], pesticide injections [45][46][47], or even mechanical pest destruction. The Internet of Things and sensors provide farmers with real-time information on soil parameters, temperature, gases in the air, weather conditions, and many other parameters, which are often passed to cloud infrastructures and can then be used for analysis and prediction [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%